Acceptability of the R21/Matrix-M malaria vaccine alongside existing malaria interventions in the trial context - Jayne Webster; Brian Greenwood; Daniel Chandramohan; Alassane Dicko; Issaka Sagara; Djibrilla Issiaka; Adrian VS Hill; Halimatou Diawara; Fatoumata Koita; Seydou Traoré; Jane Grant; Mehreen Datoo; et al. (BMJ Global Health)
Background The R21/Matrix-M malaria vaccine has been shown to provide high protective efficacy against malaria in a phase III trial, and has been recommended for use by WHO. The vaccine will soon be deployed at scale in sub-Saharan Africa. This study aimed to understand the caregiver and community acceptability of the R21/Matrix-M vaccine alongside existing malaria prevention interventions, according to the communities of participants in the seasonal R21/Matrix-M phase III trial in Mali.Methods Qualitative data were collected to assess the acceptability of the R21/Matrix-M vaccine alongside the three R21/Matrix-M or control vaccine priming injections given in the first year of the trial. A total of 33 in-depth interviews (IDIs), 12 focus group discussions (FGDs) and 45 exit interviews at the trial clinics were conducted with caregivers of trial participants, 18 IDIs and 8 FGDs were conducted with community members, 13 IDIs with community health workers and 8 IDIs with trial field staff. Data were coded using the constructs from Sekhon’s theoretical framework on acceptability.Results Acceptability of the R21/Matrix-M vaccine was driven mainly by the high burden of malaria in the highly seasonal study area and consequent demand for a malaria vaccine, a perceived high efficacy of the R21/Matrix-M vaccine, and a high level of trust and confidence in the trial and trial team. These perceptions of the acceptability of the R21/Matrix-M vaccine led to a reduced perceived importance of seasonal malaria chemoprevention (SMC) among some caregivers, while others viewed R21/Matrix-M, SMC and insecticide-treated nets as complementary.Conclusions The R21/Matrix-M vaccine was acceptable to caregivers and communities of participants in the R21/Matrix-M phase III trial in Mali. Implementation research is needed to evaluate and ensure co-coverage of complementary malaria control interventions, including SMC in seasonal settings, in the face of the scale-up of R21/Matrix-M and other malaria vaccines.